ACTIVE COMPOUND OF ZINGIBER CASSUMUNAR ROXB. DOWN-REGULATES THE EXPRESSION OF GENES INVOLVED IN JOINT EROSION IN A HUMAN SYNOVIAL FIBROBLAST CELL LINE - Chaiwongsa, Rujirek; Ongchai, Siriwan; Boonsing, Phorani; Kongtawelert, Prachya; Panthong, Ampai; Reutrakul, Vichai (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Rheumatoid arthritis (RA) is a chronic inflammatory disease of the synovium. It is involved in up-regulation of pro-inflammatory cytokines and matrix metalloproteinases (MMPs), resulting in joint inflammation and erosion. Zingiber cassumunar Roxb. has long been used to reduce joint pain and inflammation. This study aimed to investigate the inhibitory activities of an active compound of Z. cassumunar, (E)-4-(3’,4’-dimethoxyphenyl)but-3-en-1-ol (compound D), against cytokine-induced up-regulation of catabolic genes involved in cartilage degradation in RA. Synovial fibroblast cell line, SW982, was cultured in media containing interleukin-1ß (IL-1ß), in the presence or absence of compound D at the concentration range of 1 to 100 µM. After 24 hours, the cells were analyzed for the expressions of MMPs, IL-1ß and interleukin-1ß-converting enzyme (ICE) by RT-PCR. MMPs activities in the culture media were analyzed by zymographic techniques. Dexamethasone was used as the positive control. It was found that compound D at the concentration of 10 - 100 M significantly decreased the mRNA expressions of MMP-1, -2, -3, and -13 which was induced by IL-1ß (P<0.05) concomitantly with a decrease in activities of these MMPs in the culture media. An increase in the mRNA expression of IL-1ß and ICE was also suppressed by compound D. The results suggest that the potent activities of this compound may be involved in the reduction of IL-1ß protein synthesis in both pro-form and active form which played an important role in up-regulation of MMPs. This study first revealed the chondroprotective activity of Z. cassumunar in the transcriptional level by suppressing cytokine-induced catabolic genes which caused cartilage erosion in RA.